Valorization of cassava peels by the white rot fungus Panus tigrinus M609RQY - Ruqayyah, Tijani I.D.; Jamal, Parveen; Alam, Md Zahangir; Mirghani, Mohamed Elwathig Saeed (INSI Publications, 2011)
The upgrading of cassava peel into a nutritionally enriched animal feed by the white rot fungus Panus tigrinus M609RQY was investigated. Positive contributing media components were determined by Plackett- Burman design (PBD) and optimized by one-factor-at-a-time (OFAT) method. In the screening of media constituents, protein and lignin content were chosen as the responses from the experiments. Two media constituents, wheat flour and MgSO4, contributed positively to the responses. In the OFAT experiments, particle size was also optimized alongside the positive contributing factors from PBD. Plackett–Burman design gave 55.42% lignin degradation and 67.58% protein increase. Results from OFAT revealed the following optimum levels: Wheat flour, 4% (w/w); MgSO4, 0.7 g/kg dried cassava peel and particle size 2 mm. Under this condition, 61.66% lignin degradation and 71.31% protein increase were achieved. This study revealed the Enrichment ability of Panus tigrinus on cassava peel which can be employed in other biotechnological applications.